Edukasi Kesehatan Reproduksi Remaja untuk Menyongsong Indonesia Emas 2045 - Latifah Nuraini; Irma Nur Af'idah; Arif Chasannudin; Zukrofuz Zaim (Indonesia Berdaya, 2023)
The purpose of this community service is to increase adolescent knowledge about reproductive health, which is important for the survival of the youth, offspring, and the future of the Indonesian nation, especially in welcoming “Indonesia Emas 2045”. Adolescent reproductive health education needs to be improved considering that this knowledge is still considered taboo so it gets less attention. The method used in this service is ABCD (Asset Based Community Development) with the main assets being teenagers in Rogomulyo Kayen Pati Village while the community is the Kayen Pati District Health Office. The service steps include: 1) observation, 2) community approach, 3) socialization of activities, 4) socialize the adolescent reproductive health, 5) evaluation and mentoring. The activity was carried out by socializing knowledge, discussing, and giving questionnaires. The results obtained, the average value of the participants was 79.8, meaning that the participants' understanding of reproductive health was high. Based on the questionnaire, most of the participants obtained reproductive health information from the internet. These results are quite worrying because the internet does not only have a positive side. Reproductive health socialization should be provided starting from children, adolescents, pregnant mothers, and parents, so that this knowledge is no longer considered taboo and becomes the needs of each individual.